2020
DOI: 10.3390/molecules25204752
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Hydrochloride Decreases Fusarium graminearum Growth and Virulence and Boosts Growth, Development and Systemic Acquired Resistance in Two Durum Wheat Genotypes

Abstract: Fusarium head blight (FHB) is a devastating disease for cereals. FHB is managed by fungicides at anthesis, but their efficacy is variable. Conventional fungicides accumulate in the soil and are dangerous for animal and human health. This study assayed the antifungal ability of chitosan hydrochloride against Fusarium graminearum. Chitosan reduced F. graminearum growth and downregulated the transcript of the major genes involved in the cell growth, respiration, virulence, and trichothecenes biosynthesis. Chitosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 118 publications
1
26
2
Order By: Relevance
“…Recently, it was reported that the application of chitosan hydrochloride derived from chitin suppressed the severity of FHB and DON accumulation in wheat spikes. In addition, chitosan treatment activated the SAR signaling pathway and caused induction of some defense genes in wheat spikes [ 48 ]. Additionally, some natural products have been identified as inhibitors of trichothecene biosynthesis in F. graminearum .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that the application of chitosan hydrochloride derived from chitin suppressed the severity of FHB and DON accumulation in wheat spikes. In addition, chitosan treatment activated the SAR signaling pathway and caused induction of some defense genes in wheat spikes [ 48 ]. Additionally, some natural products have been identified as inhibitors of trichothecene biosynthesis in F. graminearum .…”
Section: Discussionmentioning
confidence: 99%
“…Research has also been conducted on durum wheat on the effect of hydrochloride chitosan. The results showed a decrease in the growth of F. graminearum [55]. Furthermore, it has been proven that in the case of wheat and barley, chitosan and isolates of Pseudomonas spp.…”
Section: Pathogen and Disease Controlmentioning
confidence: 91%
“…A decrease in growth of these Fusarium species was observed, using chitosan and water activity (aW) [124]. It also points to the huge potential of non-toxic chitosan to replace conventional antifungal agents [55]. A study on maize also found that chitosan in combination with Cuscuta pedicellata extract has the potential to be protective against Fusarium oxysporum [125].…”
Section: Pathogen and Disease Controlmentioning
confidence: 98%
See 1 more Smart Citation
“…However, no fully effective FHB fungicide is available ( Haidukowski et al, 2012 ), and the application window is very narrow, spanning just a few days around anthesis ( Mesterházy et al, 2003 ). Recently, an organic strategy to reduce FHB incidence and severity was proposed, but now it needs to be confirmed on wide areas ( Francesconi et al, 2020 ). For these reasons, early detection and control of FHB is a key factor to gain maximum protection of yield ( Mahlein et al, 2019 ) from fungal spread and mycotoxin accumulation; in fact, there is a strong evidence base in the research literature that a prompt and early application of fungicides instead of applying fungicides at late stages of infection drastically reduce the FHB spread and DON accumulation inside the grains, instead of applying fungicides at late stage of infection ( Freije and Wise, 2015 ; Feksa et al, 2019 ; Bolanos-Carriel et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%